2022
DOI: 10.3390/jmse10050570
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Downdrift Erosion by Twin Long-Range Jetties on an Open Mesotidal Muddy Coast, China

Abstract: Downdrift shoreline recession associated with the construction of a shore-crossing hard structure represents one of coastal erosional hotspots that must be addressed for an integrated, sustainable coastal zone management. To prevent siltation within the navigation channel, two rubber-mounted jetties were installed at the Sheyang River mouth on the open mesotidal muddy coast in Jiangsu province, China, in October 2013. The north jetty is 7.9 km long, while the south jetty is 7.8 km long. The net longshore sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The sediment deposition associated with jetties is one of the key topics for sustainable coastal zone management. Previous studies have reported significant beach accretion on the updrift side in response to jetty constructions (Hapke et al, 2013;Garel et al, 2015;Wang et al, 2022). Salleh and Nadzir (2020) showed that flow velocity and current direction around a jetty significantly affected the deposition of coastal sediments.…”
Section: Introductionmentioning
confidence: 96%
“…The sediment deposition associated with jetties is one of the key topics for sustainable coastal zone management. Previous studies have reported significant beach accretion on the updrift side in response to jetty constructions (Hapke et al, 2013;Garel et al, 2015;Wang et al, 2022). Salleh and Nadzir (2020) showed that flow velocity and current direction around a jetty significantly affected the deposition of coastal sediments.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, these structures, especially groins, significantly influence longshore sediment transport dynamics, often leading to morphological changes along coastlines. A common consequence of interrupting natural sand transport is the accretion of beaches updrift and erosion downdrift, exacerbating shoreline recession and threatening coastal communities and ecosystems at those locations [5,6]. This downdrift erosion, a focal point of coastal degradation, poses challenges for effective erosion management strategies, highlighting the urgency to comprehend its processes and magnitudes.…”
Section: Introductionmentioning
confidence: 99%